A credit-risk valuation under the variance-gamma asset return - Roman V. Ivanov (Risks, 2018)
This paper considers risks of the investment portfolio, which consist of distributed mortgages and sold European call options. It is assumed that the stream of the credit payments could fall by a jump. The time of the jump is modeled by the exponential distribution. We suggest that the returns on stock are variance-gamma distributed. The value at risk, the expected shortfall and the entropic risk measure for this portfolio are calculated in closed forms. The obtained formulas exploit the values of generalized hypergeometric functions.
Keywords: 330; variance-gamma distribution; credit risk; call option; exponential distribution; shortfall risk; generalized hyperbolic function